Analisis Kualitas Pelayanan dalam Pencatatan AK 1 dalam Memberikan Kepuasan kepada Masyarakat pada Dinas Transmigrasi dan Tenaga Kerja Kabupaten Aceh Singkil - Wiryadi, Rizky; Sihombing, Marlon; Isnaini, Isnaini (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2020)
As well as Factors that influence Service Quality in Recording AK I for job seekers in the Transmigration and Manpower Office of Aceh Singkil Regency. With the aim of this research is to find out the quality of service for recording I AK seen from Tangible (tangible) indicators, reliability (reliability), responsiviness (Assurance), Assurance (guarantee), and Emphaty (Empathy) in giving satisfaction to job seekers at the Transmigration and Manpower Agency Aceh Singkil Regency Work and Factors that Influence Service Quality in Recording AK I for job seekers in the Transmigration and Manpower Office of Aceh Singkil Regency. This research method uses descriptive qualitative research, to obtain an overview as the formulation of the existing problem and reveal the problem as it is in accordance with the existing reality through analysis of descriptive data from the results of interviews. The results of the study found several indicators of service quality that have not been well met, this was from the results of interviews and research observations at the research site. The reason is the lack of budget allocation and Allocation of Facilities and Infrastructure Supporting services from the Transmigration and Manpower Service to the Manpower sector which is responsible for the AK I. Recording service. Recommendations on the results of research are expected by the Transmigration and Manpower Service to establish AK I Registration Services Unit which has its own facilities and infrastructure. and fulfill human resources who are skilled in the field of services.